2010
DOI: 10.1073/pnas.1006572107
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of the first hyperpolarizability/bond-length alternation parameter relationship

Abstract: We have investigated the dependence of the static first hyperpolarizability on the bond-length alternation (BLA) parameter. Our analysis indicates that the validity of the first hyperpolarizability/BLA parameter relationship is restricted to the no-field, vacuum, limit, while it successively breaks down along with increasing polarity of a surrounding medium, becoming invalid, for instance, in an aqueous solution. This contention is based on a series of TD-DFT, TD-DFT/PCM and hybrid TD-DFT/MM calculations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 40 publications
2
63
2
Order By: Relevance
“…This is consistent with the previously observed weak correlation between BLA and NLO properties in geometries extracted from molecular dynamics simulations. 13 In this case, the focus should be on BOA and not BLA since changes in BOA will be a …”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the previously observed weak correlation between BLA and NLO properties in geometries extracted from molecular dynamics simulations. 13 In this case, the focus should be on BOA and not BLA since changes in BOA will be a …”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…13 To provide a comprehensive understanding of this question, we elucidate here the limits of when the commonly used relationships between BLA and the molecular NLO properties are applicable. In particular, we demonstrate that BLA and BOA are well correlated only when the molecular geometry is optimized in the environment of interest.…”
mentioning
confidence: 99%
“…The d T max values of BMVC-C1, BMVC-C2, and BMVC-C3 gradually increase as the electron-donating capability of the substituent increases. The transitions corresponding to their maximal The NLO response is closely related to the bond length alternation (BLA) [36,37], which is defined as the average difference in length between the single and double bonds in the molecule. We calculated the BLA values of the BMVC-I molecules and compared the behavior of the TPA crosssection and BLA for the molecules studied.…”
Section: Two-photon Absorption Propertiesmentioning
confidence: 99%
“…7 We recently pursued a radically different approach to enhance γ, namely twisted π-systems 8 and showed that chromophore TMC-2 (Figure 1), despite its relatively compact size and conjugation length, exhibits greater third-order NLO response than many planar dyes of comparable or greater π-expanse. 9 Closely spaced TMC-2 zwitterionic states greatly reduce the denominator energy terms [eq.…”
mentioning
confidence: 99%